The Influence of Role Modeling and Rewards on Teacher Discipline at State Elementary School 2 Tanjungsamak - Kamal; Musnar indra Daulay; Imam Hanafi (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This study aims to analyze the influence of role models and reward provision on teacher discipline at State Elementary School 2 Tanjungsamak. The method used in this study is a quantitative approach with multiple linear regression analysis techniques. Data were collected through questionnaires distributed to teachers at the school. The results of the study indicate that both role models and reward provision have a significant influence on teacher discipline. However, reward provision shows a stronger correlation with teacher discipline than role models. This indicates that an effective reward system can increase teacher motivation and discipline more directly. The conclusion of this study emphasizes the importance of developing a fair and transparent reward system in schools, as well as improving the quality of leadership to form a strong culture of discipline.